Conquering myositis, beyond remission - Amber O'Connor; T G Sundaram (Indian Journal of Rheumatology)
Akin to a stowed sailboat, limiting management of chronic illnesses such as idiopathic inflammatory myopathies (IIM) to diagnosis, investigations, and drug prescriptions, is like leaving the seas unchartered. The importance of holistic care, including psychological and social support, cannot be overemphasized. In the face of adversity, patients seek refuge in friends and kin for emotional support. In such times, mutual support from others with common experiences has great potential in improving management. In this era of borderless e-communication, online patient communities are paving the road for wholesome and holistic care to bring about a positive change in patients' lives. Through this interview with Amber O'Connor, who not only survived, but conquered IIM over 16 long years, we take you through the oft-ignored realms of patient awareness, education, support communities, the power of being understood, and the transformative effect these little things can have in enriching patients' lives.